Food Security and Trade Liberalization: A Strategic Approach for Indonesia - Jumarni Fare; Pudji Astuty (PT. ALHAFI BERKAH INDONESIA, 2025)
Indonesia, as one of the largest food-importing nations globally, experiences significant volatility in domestic food prices driven by global market fluctuations. The liberalization of trade, particularly in the agriculture sector, has generated mixed outcomes. While empirical studies highlight potential welfare gains, the benefits are disproportionately skewed toward developed countries, leaving developing economy increasingly dependent on food imports. Strategic commodities such as rice, maize, soybeans, and sugar are especially vulnerable, raising concerns over national food security. Moreover, food security in Indonesia encompasses a multi-dimensional framework, involving not only supply and access, but also household-level consumption patterns and state interventions. In light of these dynamics, this paper argues for the formulation of commodity-specific and temporally responsive food security policies. It emphasizes the integration of theoretical and empirical models that incorporate both global trade realities and localized policy responses to ensure sustainable and equitable food resilience in the context of liberalized markets.